Discovery of a Trough Xylophone in Northern Mozambique - Kubik, Gerhard (International Library of African Music, 1963)
The discovery of a trough xylophone near Lake Chilwa in Northern Mozambique might be of some interest to students of relations between Indonesian and African Music.would like if my short article could be taken as a travellers account only and not as the expression of any attitude towards a particular theory.It was by chance that we came to find Mario Santu, player of a trough xylophone on the 4th of October, 1962, some 2 kms. east of a small place called Chitambo on the road from Milango to Molumbo.Arriving at the house, I saw a large trough xylophone standing in the shade of the grass roof and the owner and player, a man of perhaps 35 years, saluted us.The kind of xylophone played by Mario is called Mambira2, according to his own indication and that of many other people at Chitambo. It had seventeen keys of a light coloured wood. The keys were placed over a trough-like resonator, which, however, was not one piece of wood, but consisted of five parts nailed together.
Keywords: Ethnomusicology; Xylophone music; Xylophone; Musical instruments; Mozambique; African Music; Xylophone (Instrument)